Creación de Add-on Facturación Electrónica en Zoho. - Alvarado-Gómez, Cristian (Instituto Tecnológico de Costa Rica, 2019)
Technology implementations in companies seek to streamline and simplify processes to keep better control of it and increase productivity. In this case, the accounting department of the software development company Centauro Solutions has the need to manage in a better way the electronic invoicing process since currently, they use two systems to carry out this process, generating an additional expenditure of time and resources that could be utilized in other tasks. Given the above, a 16-week work was carried out, where the various processes of engineering development of the software were implemented, oriented in the construction of a solution for the billing process. These processes correspond to the proposal of a solution, definition of the requirements, design of a software platform, and development of the software platform and control of the quality of the elaborated platform. With this, a solution was obtained that allows to manage the electronic invoicing processes and to carry the accounting part from the same system.
Práctica de especialidad (Bachillerato en Ingeniería en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2019.
Keywords: Tecnología de la información; Control financiero; Software; Requerimientos; Aseguramiento de la calidad; Information technology; Financial control; Requirements; Quality assurance; Research Subject Categories::TECHNOLOGY::Information technology